Typification of names and nomenclatural notes on the South Andean and Patagonian species of Polygala Linnaeus (Polygalaceae) - Martinez, Agustina; Zuloaga, Fernando Omar; Pastore, Jose Floriano B. (Phytotaxa, 2018)
As part of an ongoing revision of the genus Polygala, several names of the South Andean and Patagonian species in need of nomenclatural and taxonomic study were identified. 13 lectotypes have been designated for accepted names, synonyms and a dubious taxon.